Modeling, numerical simulation and validation of a convective dryer in steady conditions: case study of tropical woods. (3rd March 2020) - Simo-Tagne, Merlin; Bennamoun, Lyes; Léonard, Angélique; Rogaume, Yann
ABSTRACT: This paper presents a modeling and a numerical study that allows following the variation of the moisture content, temperature, drying rate and heat and mass transfer coefficients of four African tropical woods coming from Douala Cameroon. Experimental setup was developed in order to verify the drying curves and calculation of mass and heat transfer coefficients for both moisture content gradient and temperature gradient. The thermophysical properties were selected after performing an exhaustive literature review linked to the tested materials. The drying conditions were 25°C, 33.5°C and 0.25 m/s, representing wet temperature, dry temperature and air velocity, respectively. Wood thickness ranged between 22 and 25 mm. According to modeling and simulation results, the predicted moisture content shows an average relative error on each drying curve less than 10% compared to the experimental results. Mass and heat transfer coefficient evolutions are physically explained with satisfaction. Mass transfer coefficients for temperature gradient can be neglected in steady drying conditions as compared to the other transfer coefficients. Water permeability and brake factor of diffusivity of the air vapor in wood are determined using an inverse method. The presented drying model can be used to simulate in particular the tropical woods drying.